The Pendulum
VIII, 542 p.
Keywords: The pendulum is a universal topic in primary and secondary schools, but its full potential for learning about physics, the nature of science, and the relationships between science, mathematics, technology, society and culture is seldom realised. Contributions to this 32-chapter anthology deal with the science, history, methodology and pedagogy of pendulum motion. There is ample material for the richer and more cross-disciplinary treatment of the pendulum from elementary school, to high school, and through to advanced university classes. Scientists will value the studies on the physics of the pendulum; historians will appreciate the detailed treatment of Galileo, Huygens, Newton and Foucault’s pendulum investigations; psychologists and educators will learn from the papers on Piaget; teachers will welcome the many contributions to pendulum pedagogy. All readers will come away with a new awareness of the importance of the pendulum in the foundation and development of modern science; and for its centrality in so many facets of society and culture. .